2008
DOI: 10.1097/brs.0b013e31817b8f53
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Mesenchymal Stem Cells in the Chemical Microenvironment of the Intervertebral Disc

Abstract: Study Design Responses of mesenchymal stem cells (MSCs) from 2 age groups was analyzed under chemical conditions representative of the intervertebral disc (IVD) (low glucose levels, acidic pH, high osmolarity, and combined conditions). Objective To determine the microenvironmental conditions of the IVD that are critical for MSC-based tissue repair and to determine whether MSCs from different age groups respond differently. Summary of Background Data MSCs offer promise for IVD repair, but their potential is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
151
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 37 publications
9
151
1
3
Order By: Relevance
“…Nevertheless, low oxygen tension and hydrostatic pressure alone without TGF-b could not initiate chondrogenesis of MSC [105]. A low glucose condition stimulates anabolic gene expression of MSCs [128]. An acidic environment and high osmolarity, as in the IVD, decrease MSC proliferation and viability, alter MSC morphology and inhibit anabolic gene expression [126,128].…”
Section: Ivd Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, low oxygen tension and hydrostatic pressure alone without TGF-b could not initiate chondrogenesis of MSC [105]. A low glucose condition stimulates anabolic gene expression of MSCs [128]. An acidic environment and high osmolarity, as in the IVD, decrease MSC proliferation and viability, alter MSC morphology and inhibit anabolic gene expression [126,128].…”
Section: Ivd Tissue Engineeringmentioning
confidence: 99%
“…A low glucose condition stimulates anabolic gene expression of MSCs [128]. An acidic environment and high osmolarity, as in the IVD, decrease MSC proliferation and viability, alter MSC morphology and inhibit anabolic gene expression [126,128]. Overall, the disc environment certainly contains not only factors that favour MSC differentiation towards matrix producing cells but also factors that may hinder MSC survival.…”
Section: Ivd Tissue Engineeringmentioning
confidence: 99%
“…Numerous stem cell types have been used in the field of cell transplantation for the treatment of IDD, such as bone marrow-derived stem cells (BMSCs) (10), adipose-derived MSCs (ADMSCs) (11), human umbilical tissue-derived cells (12) and synovium-derived stem cells (13 (14,15). Certain studies have reported that these stem cells lack viability, proliferation and matrix biosynthesis under conditions resembling the IVD microenvironment, which negatively influences the biological and metabolic vitality of stem cells and impairs their repair potential (16,17). In recent years, increasing evidence supported the existence of nucleus pulposus MSCs (NPMSCs) in the nucleus pulposus (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Cells are then out of their native tissue which can provide cues, through cell-matrix interactions, that may alter cells' response to www.ecmjournal.org E Potier et al Notochordal cells for IVD regeneration stimulation. The culture system did not include the disc environmental factors, such as low pH or high osmolarity, showed to affect cell behaviour, especially that of BMSCs (Wuertz et al, 2008). Another limitation may be the use of a cross-species model.…”
Section: Wwwecmjournalorg E Potier Et Al Notochordal Cells For Ivdmentioning
confidence: 99%